Effect of Salary and Work Environment on Productivity (Study of Human Resource Management Literature) - Mahaputra, M. Ridho (International Journal of Advanced Multidisciplinary, 2022)
The Literature Review Review of Salaries and Work Environment on Productivity is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resources Management . The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Wages have an effect on Productivity; and 2) Work Environment has an effect on Productivity. Apart from these 2 exogenous variables that affect the endogenous variables of Productivity, there are still many other factors including the variables of Co-Workers, Leader and Workload.